2010
DOI: 10.1002/jrs.2514
|View full text |Cite
|
Sign up to set email alerts
|

Detailed analysis of the charge transfer complex N,N‐dimethylaniline–SO2 by Raman spectroscopy and density functional theory calculations

Abstract: Although the amine sulfur dioxide chemistry was well characterized in the past both experimentally and theoretically, no systematic Raman spectroscopic study describes the interaction between N,N-dimethylaniline (DMA) and sulfur dioxide (SO 2 ). The formation of a deep red oil by the reaction of SO 2 with DMA is an evidence of the charge transfer (CT) nature of the DMA-SO 2 interaction. The DMA-SO 2 normal Raman spectrum shows the appearance of two intense bands at 1110 and 1151 cm −1 , which are enhanced when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The FT‐IR and FT‐Raman spectra of 4‐hydroxy‐3‐(3‐oxo‐1‐phenylbutyl)‐2 H ‐1‐benzopyran‐2‐one (Warfarin) were measured and calculated by Amalanathan, Joe and Kostova . Ando, Matazo and Santos carried out a systematic Raman experimental and theoretical spectroscopic study of the interaction between N , N ‐dimethylaniline (DMA) and sulfur dioxide (SO 2 ), where the formation of a deep red oil by the reaction of SO 2 with DMA is an evidence of the charge transfer nature of the DMA–SO 2 interaction . Anto and coworkers measured and analyzed the FT‐IR and FT‐Raman spectra of phenylphosphate disodium salt, and they also measured the SERS spectrum as a silver colloid .…”
Section: Vibrational Studies In Chemistrymentioning
confidence: 99%
“…The FT‐IR and FT‐Raman spectra of 4‐hydroxy‐3‐(3‐oxo‐1‐phenylbutyl)‐2 H ‐1‐benzopyran‐2‐one (Warfarin) were measured and calculated by Amalanathan, Joe and Kostova . Ando, Matazo and Santos carried out a systematic Raman experimental and theoretical spectroscopic study of the interaction between N , N ‐dimethylaniline (DMA) and sulfur dioxide (SO 2 ), where the formation of a deep red oil by the reaction of SO 2 with DMA is an evidence of the charge transfer nature of the DMA–SO 2 interaction . Anto and coworkers measured and analyzed the FT‐IR and FT‐Raman spectra of phenylphosphate disodium salt, and they also measured the SERS spectrum as a silver colloid .…”
Section: Vibrational Studies In Chemistrymentioning
confidence: 99%
“…The result of present research was also compared to the other investigations in the pool of literature available (Table ). Ando et al explained the charge transfer of complex DMA and SO 2 system through Raman spectroscopy. Absorption of SO 2 into DMA solution gives an ionic liquid (dimethyl ammonium N,N ‐dimethyl amino sulfinate) .…”
Section: Resultsmentioning
confidence: 99%
“…Ando et al explained the charge transfer of complex DMA and SO 2 system through Raman spectroscopy. Absorption of SO 2 into DMA solution gives an ionic liquid (dimethyl ammonium N,N ‐dimethyl amino sulfinate) . The present work showed that DMA solution can be used as an efficient absorbent for SO 2 removal.…”
Section: Resultsmentioning
confidence: 99%
“…The charge transfer interaction from a Lewis base to SO 2 causes a partial filling of the S = O antibonding π* orbitals, and as a consequence, the S = O bond orders decrease. Therefore, the charge transfer extent to SO 2 can be monitored by vibrational spectroscopic techniques by the direct analysis of its stretching vibrational modes . Furthermore, such charge transfer interaction is associated to a highly allowed electronic transition in the near ultraviolet or visible region, permitting the use of resonance Raman spectroscopy technique.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, such charge transfer interaction is associated to a highly allowed electronic transition in the near ultraviolet or visible region, permitting the use of resonance Raman spectroscopy technique. In fact, a huge resonance Raman enhancement is associated to the ν s (SO 2 ) in SO 2 complexes, making the spectral analysis much simpler as other Raman bands are not enhanced in the same extent …”
Section: Introductionmentioning
confidence: 99%